2023
DOI: 10.3390/land12091678
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Variation and Development Stage of CO2 Emissions of Urban Agglomerations in the Yangtze River Economic Belt, China

Qikai Lu,
Tiance Lv,
Sirui Wang
et al.

Abstract: As the world’s largest developing country, China has played an important role in the achievement of the global CO2 emissions mitigation goal. The monitoring and analysis of CO2 emissions in the Yangtze River Economic Belt (YREB) urban agglomerations is strategic to the carbon peak and carbon neutrality in China. In this paper, we revealed the spatial and temporal variations of CO2 emissions in Cheng-Yu urban agglomeration (CY-UA), Yangtze River Middle-Reach urban agglomeration (YRMR-UA), and Yangtze River Delt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Some studies have focused on the temporal and spatial variations in urban CO 2 emissions themselves, such as those by Lu et al [37] and Chen et al [38]. Lu, Lv, Wang, and Wei [37] found a declining trend in CO 2 emissions in the urban agglomerations of the Yangtze River Economic Belt.…”
Section: Factors Influencing Co 2 Emissions In Cities Along the Yangt...mentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have focused on the temporal and spatial variations in urban CO 2 emissions themselves, such as those by Lu et al [37] and Chen et al [38]. Lu, Lv, Wang, and Wei [37] found a declining trend in CO 2 emissions in the urban agglomerations of the Yangtze River Economic Belt.…”
Section: Factors Influencing Co 2 Emissions In Cities Along the Yangt...mentioning
confidence: 99%
“…Some studies have focused on the temporal and spatial variations in urban CO 2 emissions themselves, such as those by Lu et al [37] and Chen et al [38]. Lu, Lv, Wang, and Wei [37] found a declining trend in CO 2 emissions in the urban agglomerations of the Yangtze River Economic Belt. Chen, Tan, Mu, Wang, Chen, and He [38] focused on the synergistic relationship between pollution and carbon emissions, finding that the level of synergy between pollution control and carbon reduction in cities along the Yangtze River Economic Belt is on the rise.…”
Section: Factors Influencing Co 2 Emissions In Cities Along the Yangt...mentioning
confidence: 99%
“…In summary, there is still some controversy among many scholars as to whether China can achieve the goals of carbon peaking and carbon neutrality on time, and there are some areas for improvement in the analysis of carbon peaking at the basin level [15]. This study uses the provinces and cities through which the South-to-North Water Diversion Project passes as the study area to analyze, build models, and carry out prediction analyses to provide the government with corresponding carbon peak strategies.…”
Section: Introductionmentioning
confidence: 99%
“…They proposed reversing the ecological fragility of the Yangtze River Basin through pollution control, ecological restoration, low carbon transformation, introduction of capital, and realization of the value of ecological services. Qikai Lu et al [ 10 ] measured carbon emissions in three urban agglomerations in the Yangtze River Economic Belt and found that carbon emissions showed a trend of increasing and then decreasing from 2008 to 2017, with emissions decreasing significantly after 2017. He [ 11 ] pointed-out that provinces and cities along the Yangtze River Economic Belt lacked management and policy regulations for collaborative governance, and constructed a diversified collaborative governance system from organization, value, market, cost, and benefits in order to integrate environmental governance and green development.…”
Section: Introductionmentioning
confidence: 99%